PENINGKATKAN HASIL BELAJAR PKN MATERI PERAN INDONESIA DI NEGARA-NEGARA ASEAN MELALUI MODEL GROUP TO GROUP EXCHANGE PADA PESERTA DIDIK KELAS VI.A SD NEGERI PALEMBANG - Rohana, Rohana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The purpose of this research is to improve Civics learning outcomes through the Group To Group Exchange method learning model for class VI.A students SD Negeri 55 Palembang. The location where research is carried out is known as the place of research and data collection. This research took place at SD Negeri 55 Palembang on Jalan Jenderal Bambang Utoyo Palembang. This research was conducted from February to April 2017. The research subjects were class VI.A students at SD Negeri 55 Palembang with a total of 27 students. It can be concluded that the Group To Group Exchange method has a positive impact on improving students' Civics learning outcomes as evidenced by an increase in student learning completeness in each cycle, based on the results of the learning activities carried out. for two cycles and all the discussions and analyzes carried out on students, namely the pre-cycle of 25.93 percent, the first cycle of 48.15 percent, and the second cycle of 88.89 percent.